Transformasi Digital Usaha Mikro Mendukung Ekonomi Digital - Utami, Novelia; Sitorus, Onny Fitriana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Microbusinesses contribute to the country's economy, so attention is needed to improve businesses in the digitalization era. Limited competence, facilities, and infrastructure are obstacles to digitalization; therefore, mentoring is required for digital transformation. This study aims to observe the digital transformation's success through mentoring activities. The research method used is qualitative, with observation, interviews, and documentation conducted with five sources who have been assisted in the digital micro business transformation. The study results show that the digital transformation that MSMEs have carried out has gone through 3 (three) stages. Namely, the first is digital competence, namely understanding the importance of digitalization and digitalization media; the second is digitalization of businesses by determining the use of digital media and the effectiveness of the use of digital media that has been used; and the third is digital transformation, namely efforts to improve businesses by innovating so that they continue to survive and grow by expanding their networks. Micro business actors who have been assisted can see the results within 2 weeks. Although insignificant, the benefits can be felt with the presence of online customers and increased customers due to the ease of transactions.